What types of political regimes subsidize fuel consumption?. (March 2022) - Fails, Matthew D.
Highlights: Non-democracies that hold multiparty elections are associated with larger gasoline consumption subsidies. Increases in value of oil and gas production leads to larger increases in subsidies in these electoral authoritarian regimes. Political benefits of gasoline subsidies make reform efforts more difficult. Abstract: Recent studies suggest that political institutions have little impact on the size of consumer fossil fuel subsidies, concluding instead that subsidies reflect country-specific and slowly changing economic factors. Such findings bode poorly for reforming these costly policies. I argue that this conclusion stems from an overly narrow view of the kinds of non-democratic regimes that exist. I introduce a large literature from political science that distinguishes "electoral authoritarian" regimes from other non-democracies and develop a theoretical argument connecting the former's reliance on broad-based public support to higher levels of fossil fuel subsidies. I test the argument using a price-gap measure of domestic consumer gasoline subsides for more than 160 countries for most years between 1990 and 2014. The results demonstrate that the emergence of electoral authoritarianism is associated with larger fuel subsidies, and that an increase in hydrocarbon production revenue has a larger impact on the size of subsidies within electoral authoritarian systems than in other regime types. Reform efforts must acknowledge this political logic while focusing on how to offset subsidies with less environmentally harmful measures.